Integrating World Experience Through Interdisciplinary Learning in Nigerian Universities - Olanrewaju, Muraina Kamilu; Musa, Hadiza A.; Tinuke, Kamaldeen Rahmat (Bumi Publikasi Nusantara, 2023)
In the current context, higher education faces the challenge of preparing future professionals to respond to society’s increasingly complex problems. However, the search for solutions means adopting new ways of working that promote multidimensionality through collaboration and an interdisciplinary outlook. Despite the advances made in interdisciplinary research, innovation development, and interdisciplinary teamwork, however, the implementation of this approach in higher education is still very slow, and further efforts are required. This article considers the opportunities for an interdisciplinary approach to student learning in university settings. In Nigeria, it is common knowledge that the educational system in it is not what it ought to be. This is evidenced by the fact that, above all, a good number of graduates from this system are unemployable, leading to so many ills in society. It is not unconnected with this fact that national policy on education was formulated to correct the anomaly. A juxtaposition of the policy with the state of higher education in Nigeria shows that the policy is far from actualizing its ends. The paper, therefore, suggested that core subjects should be integrated into the curriculum across levels that involve interdisciplinary learning in Nigerian universities.